2019
DOI: 10.1038/s41598-019-48069-5
|View full text |Cite
|
Sign up to set email alerts
|

Photocapacitive CdS/WOx nanostructures for solar energy storage

Abstract: Through a facile solvothermal procedure, a CdS/WO x nanocomposite has been synthesised which exhibits photocapacitive behaviour under white light illumination at a radiant flux density of 99.3 mW cm −2 . Photoelectrochemical experiments were undertaken to examine the self-charging properties of the material and to develop an understanding of the underlying electronic band structure responsible for the phenomenon. By employing XPS, UPS and UV-Vis diffuse reflectance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 150 publications
0
11
0
Order By: Relevance
“…In particular, the outlined comparison of EIS behaviours suggests that whilst a selection of equivalent circuit elements are required to describe the measured impedance behaviours, these components may be regarded as approximately independent of irradiance levels or bias potential, with the exception of the series resistance Rin. In a previous publication by the present authors [27] it was demonstrated that the open-circuit potential of CdS/WOx becomes increasingly negative when exposed to white light, and hence it follows from the EIS analysis that this incident irradiation can be approximately described as a conventional source of voltage and current in series with the equivalent circuit shown in Fig. 7.…”
Section: Electrochemical Impedance Measurementsmentioning
confidence: 58%
See 3 more Smart Citations
“…In particular, the outlined comparison of EIS behaviours suggests that whilst a selection of equivalent circuit elements are required to describe the measured impedance behaviours, these components may be regarded as approximately independent of irradiance levels or bias potential, with the exception of the series resistance Rin. In a previous publication by the present authors [27] it was demonstrated that the open-circuit potential of CdS/WOx becomes increasingly negative when exposed to white light, and hence it follows from the EIS analysis that this incident irradiation can be approximately described as a conventional source of voltage and current in series with the equivalent circuit shown in Fig. 7.…”
Section: Electrochemical Impedance Measurementsmentioning
confidence: 58%
“…By investigating the transient photocurrent response (TPR) of the CdS/WOx nanocomposite in the presence of aqueous sodium sulphate (0.5 M), it was demonstrated in a previous publication by the present authors [27] that the addition of WOx could be exploited to increase photocurrent under one Sun irradiation by an order of magnitude relative to CdS alone. However, significant electrode instability was evident during the course of these experiments, with the photocurrent halving over a period of approximately twenty minutes from the onset of illumination.…”
Section: Transient Photocurrent Response (Tpr)mentioning
confidence: 77%
See 2 more Smart Citations
“…−1.0 V vs. Ag/AgCl), due to the higher conduction band of TPE-Ca. The photocurrent density of CdS/TPE-Ca (2.55 mA cm −2 ) can be compared to the recent developed CdS/MoS 2 (1.9 mA cm −2 ) [41], CdS/WO x (10 µA cm −2 ) [42], and CdS nanowires (2.0 mA cm −2 ) [43]. Subsequently, the electrochemical impedance spectroscopy (EIS) Nyquist plots was conducted to demonstrate the electrochemical kinetics toward the interfaces between samples and electrolyte.…”
Section: Photoelectrochemical Cellmentioning
confidence: 99%